2013
DOI: 10.1016/j.bpj.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Vinculin in Ventricular Myocyte Mechanics and Dysfunction

Abstract: Vinculin (Vcl) plays a key structural role in ventricular myocytes that, when disrupted, can lead to contractile dysfunction and dilated cardiomyopathy. To investigate the role of Vcl in myocyte and myocardial function, cardiomyocyte-specific Vcl knockout mice (cVclKO) and littermate control wild-type mice were studied with transmission electron microscopy (TEM) and in vivo magnetic resonance imaging (MRI) tagging before the onset of global ventricular dysfunction. MRI revealed significantly decreased systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…This is relevant because a significant reduction of Vcl expression at costameres, as well as irregular alignment of Vcl at intercalated discs has been observed after Trypanosoma cruzi infection (Melo et al, 2004). Recently, it has been shown that Vcl deficiency increased systolic stiffness, by increasing interfilament spacing, and thereby could induce mechanical stress in sarcomeres (Tangney et al, 2013). These reports all illustrate the role of Vcl as a cardiomyopathy-linked gene.…”
Section: Discussionmentioning
confidence: 89%
“…This is relevant because a significant reduction of Vcl expression at costameres, as well as irregular alignment of Vcl at intercalated discs has been observed after Trypanosoma cruzi infection (Melo et al, 2004). Recently, it has been shown that Vcl deficiency increased systolic stiffness, by increasing interfilament spacing, and thereby could induce mechanical stress in sarcomeres (Tangney et al, 2013). These reports all illustrate the role of Vcl as a cardiomyopathy-linked gene.…”
Section: Discussionmentioning
confidence: 89%
“…Computational studies have suggested a role for vinculin in regulating sarcomere lattice spacing and contractility (28). Therefore, electron micrographs of cross sections through VincHE and control cardiac myofibrils were examined to investigate alterations in ultrastructure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since alterations to the cardiac sarcomere lattice structure have been postulated to change the contractile efficiency, 27 we next determined whether VincHE flies had altered cardiomyocyte bioenergetics by adapting the Seahorse XF24 extracellular flux analyzer to measure respiration of individual, surgically exposed and contracting hearts. Oxygen consumption rate (OCR) was proportional to the number of hearts assayed, though we obtained sufficient signal with a single heart, allowing us to measure fly-to-fly variation [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 Better cycling alters energy requirements in the heart, but it was uncertain if similar changes could be observed systemically. Untargeted whole fly GC-MS revealed significant energy metabolite accumulation for VincHE flies in all ontological clusters with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation